An accurate numerical method for systems of differentio-integral equations associated with multiphase flow - Shu, Jian Jun (2011)
An accurate numerical method which is applicable to systems of differentio-integral equations with quite general boundary conditions has been developed. The method is a useful extension of the Keller box scheme designed to facilitate the solution of differential systems involving integral operators which naturally aris in multiphase flows. A combination of merging and reduction procedures is introduced to handle the multilayer and integral operator features of such problems. The development of the method is demonstrated in the context of laminar film condensation in the presence of both external forcing and body forces.